PEMBUATAN PRODUK HERBAL BAWANG PUTIH DENGAN FERMENTASI - Ida Febriana; Fadarina; Jaksen; Rima Daniar (Aptekmas Jurnal Pengabdian pada Masyarakat, 2023)
Garlic has properties for health, such as preventing the presence of bacteria and cancer, garlic contains allicin compounds and contains vitamin C, where these compounds can boost the immune system to fight germs. Therefore, garlic can be alternative to maintain endurance, by fermenting it into a garlic herbal product counseling aims to foster creativity, and create anattitude of caring for the environment, as well as understanding the positive impact of natural resource processing on the environment, health, social and especially the economy. This community service activity is also carried out to help take advantage of the potential of partner areas and help increase the income of the local community, as an alternative creativity in overcoming the direct impact of post-Covid-19 on the economic aspect. Counseling in the form of presentations, short lectures, and demonstrations with the production of black garlic.